To stay or not to stay: The stability of choice perseveration in value-based decision making. Issue 1 (January 2021) - Senftleben, Ulrike; Schoemann, Martin; Rudolf, Matthias; Scherbaum, Stefan
In real life, decisions are often naturally embedded in decision sequences. In contrast, in the laboratory, decisions are oftentimes analysed in isolation. Here, we investigated the influence of decision sequences in value-based decision making and whether the stability of such effects can be modulated. In our decision task, participants needed to collect rewards in a virtual two-dimensional world. We presented a series of two reward options that were either quick to collect but were smaller in value or took longer to collect but were larger in value. The subjective value of each option was driven by the options' value and how quickly they could be reached. We manipulated the subjective values of the options so that one option became gradually less valuable over the course of a sequence, which allowed us to measure choice perseveration (i.e., how long participants stick to this option). In two experiments, we further manipulated the time interval between two trials (inter-trial interval), and the time delay between the onsets of both reward options (stimulus onset asynchrony). We predicted how these manipulations would affect choice perseveration using a computational attractor model. Our results indicate that both the inter-trial interval and the stimulus onset asynchrony modulate choice perseveration as predicted by the model. We discuss how our findings extend to research on cognitive stability and flexibility.